PRescriptiOn PattERns of Oral Anticoagulants in Nonvalvular Atrial Fibrillation (PROPER study). (May 2017) - Basaran, Ozcan; Filiz Basaran, Nesrin; Cekic, Edip Guvenc; Altun, Ibrahim; Dogan, Volkan; Mert, Gurbet Ozge; Mert, Kadir Ugur; Akin, Fatih; Soylu, Mustafa Ozcan; Memic Sancar, Kadriye; Biteker, Murat
Introduction: Inappropriate use of oral anticoagulants (OACs) have not been well investigatedand, however, may be frequent in real-world practice in patients with nonvalvular atrial fibrillation (NVAF). This study was designed to evaluate the prescription patterns and appropriateness of OACs in patients with NVAF in real-world clinical settings. Methods: We performed a prospective, observational study (NCT02366338). A total of 148 patients with NVAF were screened for OAC prescription. Appropriateness of prescribing was evaluated using 9 criteria of the Medication Appropriateness Index (MAI): indication, choice, dosage, modalities and practicability of administration, drug–drug interactions, drug–disease interactions, duplication, and duration. For each criterion, the evaluator has to rate whether the medication is (A) appropriate, (B) inappropriate but with limited clinical importance, and (C) inappropriate. Results: Of 148 patients, 73 (50%) were on warfarin (group 1), 39 (26%) were on rivaroxaban (group 2), and 36 (24%) were on dabigatran therapy (group 3). The MAI showed that 83% of group 1, 28% of group 2, and 47% of group 3 patients had at least 1 inappropriate criterion. Moreover, according to the choice criterion, 37% of group 1, 8% of group 2 and 5% of group 3 were rated as inappropriate, and dosage was not appropriate in 77% of group 1, 23% of group 2, and 42% of group 3. Conclusion: Inappropriate drug use is frequent among patients with NVAF not only for warfarin but also for NOACs. Although there is an apparent improvement in thromboprophylaxis of NVAF, much more effort is needed for appropriate use of OACs.